First specimen-based Indonesian record of the Wongat Dragonet Callionymus zythros Fricke, 2000 (Actinopterygii, Perciformes, Callionymidae) from Saparua Island, the Moluccas - Ruby V. Kusumah; Gino V. Limmon; Agus Priyadi; Dwi Febrianti; Kunto Wibowo (Check List)
A single male dragonet (32.3 mm standard length) (Callionymidae), collected from Saparua Island, the Moluccas Islands, Indonesia, is identified as Callionymus zythros Fricke, 2000. This specimen is the westernmost record of the species, which was previously known only from two localities, Wongat Island, Madang, Papua New Guinea and Raja Ampat Islands, West Papua, Indonesia.